Proposta metodológica para modelagem microscópica de interseções semaforizadas multimodais - Martín, Lisel Expósito (2018)
Traffic congestion problems in large cities have been increasing in recent years, so have the efforts from public management to search for possible road-related solutions, aimingto improve the efficiency and quality of both motorized and non-motorized. Following this trend, the literature has presented a paradigm shift in the planning and operation of multimodal traffic. Traffic microsimulation tools allow the analysis of several scenarios in which different transport modes operate simultaneously, bringing greater complexity and representation capability to the analysis. In order to do so, these models need to be calibrated, and the literature has shown that not enough attention has seen given to the calibration of multimodal signalized intersections. As an alternative to microsimulation modeling there are the models proposed by the Highway Capacity Manual-HCM, whose assumptions may not be satisfactorily met in reality. Given the above, the main objective of this study is to develop a methodology for the microscopic modeling of multimodal urban intersections. For this, the proposed methodology consists of three major steps: the first one is Model Construction; the second step is Calibration; while the third one is based on the comparison between the results estimated by the microscopic simulation and by the methodology proposed by the HCM. The proposed method was applied to a multimodal signalized intersection in Fortaleza and the VISSIM 9 traffic simulation software was selected to perform the microscopic modeling. The results showed that the macroscopic approach of HCM resulted in an overestimation of the delay observed in the field, while VISSIM modeling resulted in lower errors. It is believed that the proposed method presented in this research provides a better representation of traffic in multimodal signalized intersections.